ТАЛАБАЛАРДА АЛГОРИТМИК ФИКРЛАШНИ РИВОЖЛАНТИРИШ ТЕНДЕНЦИЯЛАРИ - Айтимбетов, Ю.М. (SCIENCE and SOCIETY, 2024)
The article presents the importance of the development of algorithmic thinking in students and its theoretical foundations, which analyzes the development of algorithmic thinking in students using the counting algorithm and its role in shaping students as a perfect personality.
Keywords: thinking; algorithm; algorithmic thinking; basic components of algorithmic thinking; education